PENINGKATAN KOMPETENSI KEWIRAUSAHAAN KUNCI SUKSES WIRAUSAHA - Christine Winstinindah Sandroto; Benedicta Prihatin Dwi Riyanti; Angela Oktavia Suryani; Bimo Wikantiyoso (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This community service collaborates with Atma Jaya Catholic University of Indonesia with partners to relate to entrepreneurs, namely: Institut Teknologi Del (IT Del) -North Sumatra, Universitas Negeri Makasar (UNM)-South Sulawesi, and the Universitas Persatuan Guru 1945 (UPG 1945) - East Nusa Tenggara. Community service provides competency training and coaching clinics for entrepreneurs in the Lake Toba, Makasar, and Kupang areas to improve their entrepreneurial competencies. We believe that entrepreneurial competence is the key to entrepreneurial success. The online program aims to understand the importance of increasing entrepreneurial competence to achieve business success for entrepreneurs, provide a coaching clinic for entrepreneurs who experience obstacles during the COVID-19 pandemic, and increase insight and networking among entrepreneurs in Indonesia and learn from other entrepreneurs. Training and coaching clinics are carried out following stages preparation, implementation, and evaluation, all involving university partners. The training material explains competence and dimensions of entrepreneurial competence (the ability to see opportunities, achievement motivation, and persuasion abilities). The entrepreneurship competency training and coaching clinic were well organized as expected. If the COVID-19 pandemic has been resolved, training and coaching clinics can be carried out face-to-face. Each region in Indonesia has a different culture; if the training is carried out at the location of the entrepreneurs, the topics and methods will be more specifically adapted to the culture of the entrepreneurs who are the participants.